A Handbook of Theories on Designing Alignment Between People and the Office Environment - Appel-Meulenbroek, Rianne; Danivska, Vitalija (Taylor & Francis, 2021)
Although workplace design and management are gaining more and more attention from modern organizations, workplace research is still very fragmented and spread across multiple disciplines in academia. There are several books on the market related to workplaces, facility management (FM), and corporate real estate management (CREM) disciplines, but few open up a theoretical and practical discussion across multiple theories from different fields of studies. Therefore, workplace researchers are not aware of all the angles from which workplace management and effects of workplace design on employees has been or could be studied. A lot of knowledge is lost between disciplines, and sadly, many insights do not reach workplace managers in practice. Therefore, this new book series is started by associate professor Rianne Appel-Meulenbroek (Eindhoven University of Technology, the Netherlands) and postdoc researcher Vitalija Danivska (Aalto University, Finland) as editors, published by Routledge. It is titled 'Transdisciplinary Workplace Research and Management' because it bundles important research insights from different disciplinary fields and shows its relevance for both academic workplace research and workplace management in practice. The books will address the complexity of the transdisciplinary angle necessary to solve ongoing workplace-related issues in practice, such as knowledge worker productivity, office use, and more strategic workplace management. In addition, the editors work towards further collaboration and integration of the necessary disciplines for further development of the workplace field in research and in practice. This book series is relevant for workplace experts both in academia and industry. This first book in the series focuses on the employee as a user of the work environment. The 21 theories discussed and applied to workplace design in this book address people's ability to do their job and thrive in relation to the office workplace. Some focus more on explaining why people behave the way they do (the psychosocial environment), while others take the physical and/or digital workplace quality as a starting point to explain employee outcomes such as health, satisfaction, and performance. They all explain different aspects for achieving employee-workplace alignment (EWA) and thereby ensuring employee thriving. The final chapter describes a first step towards integrating these theories into an overall interdisciplinary framework for eventually developing a grand EWA theory. The Open Access version of this book, available at http://www.taylorfrancis.com/books/e/9781003128830, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.